장년층의 자살생각 결정 요인에 관한 연구 - 윤지연(Ji-Yeon Yoon); 정규형(Kyu-Hyoung Jeong); 우현재(Hyun-Jae Woo) (인문사회과학연구, 2023)
· 연구 주제: 장년층의 자살생각 결정요인을 인구사회학적 요인, 건강 요인, 경제적 요인, 가족 요인으로 구분하여 살펴보았다. · 연구 배경: 앤 케이스와 앵거스 디턴의 절망사 논의는 거시적인 사회경제의 변화가 특정한 노동계급에게 더 절망적인 요인으로 작용했다는 것이다. 이에 상대적으로 불안정한 노동생애를 경험해온 한국 장년층의 자살생각 결정요인을 현시점에서 조명해보았다. · 선행연구와의 차이점: 한국의 베이비붐세대는 1990년대 말 외환위기를 경험하면서 상당수가 빈곤 지위로 이동하였으며, 이들은 현재 장년기 연령에 도달해 있다. 이들 세대가 본격적으로 노인인구에 진입하게 되면, 노인세대 빈곤과 불평등 문제는 더 악화될 것으로 전망된다는 점에서 본 연구는 시의성을 갖는다. · 연구방법: 본 연구는 2021년에 실시한 16차 한국복지패널조사자료를 활용하였고, 연구모형 검증을 위해 Stata 15.1과 M-plus 8.0 프로그램으로 Firth Method를 활용한 로지스틱 회귀분석을 진행하였다. · 연구결과: 장년층의 연령, 우울, 가구원 수는 자살생각에 유의한 영향을 미치는 것으로 나타났다. 한편 장년층의 학력, 취업 여부, 균등화 연소득 등은 자살생각에 유의한 영향을 미치지 않는 것으로 나타났다. · 공헌점 및 기대효과: 본 연구는 베이비붐세대의 노인인구 진입 관련 정책 수립 및 개선에 필요한 기초자료를 제공하였다. · Research topics: Determinants of Suicidal ideation in late middle-aged adults (50-64 years) were identified by dividing them into sociodemographic factors, health factors, economic factors, and familial factors. · Research background: The discusiion of deaths of despair by Anne Case and Angus Deaton is that macroscopic socioeconomic changes acted as a more desperate factor for a specific working class. Accordingly, the determinants of suicidal ideation in late middle-aged adults in Korea, who have experienced relatively unstable working life, were analyzed at this point. · Differences from prior research: Many of the baby boomers in Korea moved to poverty as they experienced a currency crisis in the late 1990s, and they are now reaching their advanced age. This study is timely in that it is expected that the problem of poverty and inequality in the elderly generation will worsen when these generations enter the elderly population. · Research method: This study used the 16th Korean Welfare Panel Study(KoWePS) in 2021, and logistic regression analysis using the Firth Method was performed with the Stata 15.1 and M-plus 8.0 programs to verify the research model. · Research results: Age, depression, and the number of household members were found to have a significant effect on suicidal ideation in late middle-aged adults. On the other hand, it was found that education, employment status, and equalized annual income did not have a significant effect on suicidal ideation in late middle-aged adults. · Contribution points and expected effects: This study provided basic data necessary for establishing and improving policies related to the baby boomer’s entry into the elderly population. KCI Citation Count: 0